(untitled) (Baghdad Science Journal, 2017)
Bacteriocin is an important antimicrobial peptide that can be used in industrial and medical fields due to its characteristics of antibacterial, food preservation and anticancer activities. Fifty isolates of Bacillus sp were collected from different soil samples which were already recognized via morphological and biochemical identification process. The isolates were screened for bacteriocin production effective against Staphylococcus spp in order to select the highest producing isolate. The isolate NK16 showed the maximum bacteriocin production (80 AU/ml) which was further characterized as Bacillus subtilis NK 16 through using API identification system (API 20E and API 50CHB). Then, next step was to detect the optimal conditions for maximum bacteriocin production which were found to be brain-heart infusion broth as the best production medium with pH 6, 30oCand 2% inoculum size. Bacteriocin was partially purified by precipitation with ammonium sulphate and then separation with sephadex G-150 gel filtration. The specific activity of the resulted partial purified bacteriocin was increased to 853.33 AU/mg with 38 fold purification and 24% yield. The study of bacteriocin characterization revealed that the activity of bacteriocin was stable after 10 min at 20, 30, 40oC whereas 50% of the bacteriocin activity was lost after exposure to 50oC and decreased to approximately 20 AU/ml at 60,70 and 80 Co. In addition, bacteriocin activity showed stability at pH 6 and 7 for 30 min while it was decreased by approximately 50% at pH 5 and 8, and completely inhibited at pH 4 and 9. On the other hand, the investigation of mode of action showed that bacteriocin has a bactericidal activity. Antimicrobial activity tests of the partial purified bacteriocin displayed a significant activity against most clinical Staphylococcus aureus and Staphylococcus epidermidis isolates, whereas it was less effective against Staphylococcus saprophyticus isolates.